1976
DOI: 10.1128/iai.13.1.44-52.1976
|View full text |Cite
|
Sign up to set email alerts
|

Phage group II staphylococcal strains with chromosomal and extrachromosomal genes for exfoliative toxin production

Abstract: Staphylococcal phage group 2 strain UT0007 was previously shown to contain a high-molecular-weight plasmid containing genes for exfoliative toxin (ET) and bacteriocin production. Phage group 2 strains UT0002 and UT0003 (Tox+Bac-) underwent a twofold and ninefold loss of ET activity, respectively, after growth at 44 C for 18 h. Strain UT0002 also lost total bacteriocin activity. Both strains contained (i) a 56S plasmid that was lost from those substrains showing reduced ET activity and (ii) a 21S plasmid with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 12 publications
2
47
0
Order By: Relevance
“…Rogolsky and his co-workers in a series of studies have attempted to define the genetic basis of ET production in S. aureus (Rogolsky et al, , 1976Warren et al, 1974Warren et al, , 1975Wiley 8z Rogolsky, 1977). In early studies no evidence was obtained for linkage of ET determinants to lysogenic phages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rogolsky and his co-workers in a series of studies have attempted to define the genetic basis of ET production in S. aureus (Rogolsky et al, , 1976Warren et al, 1974Warren et al, , 1975Wiley 8z Rogolsky, 1977). In early studies no evidence was obtained for linkage of ET determinants to lysogenic phages.…”
Section: Introductionmentioning
confidence: 99%
“…In early studies no evidence was obtained for linkage of ET determinants to lysogenic phages. The capacity to produce ET was either completely or partly lost by some strains when they were grown at high temperatures or in the presence of ethidium bromide, which suggested that a plasmid might be implicated in the expression of the toxin (Rogolsky et al, , 1976. Many toxin-producing strains also produced a bacteriocin .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) ETA protein is heterogenous in its isoelectric point, while ETB is homogenous [2]. (iii) ETA protein is coded by a chromosomal gene, but ETB is known to be coded for by a plasmid gene [7][8][9][10]. These toxins have other biological properties, such as a strict animal species specificity, age dependence, organ or tissue tropism as well as their curious immunogenicity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Two serotypes of epidermolytic toxin (ET) are specified by strains of S. aureus which cause the scalded skin syndrome [1]. Genetic studies have suggested that the gene coding for serotype A ET (eta) is chromosomal while expression of ET serotype B is plasmid-controlled [2,3]. However, these studies did not show conclusively that the etb structural gene was actually located on the plasmid because of difficulties in transferring it to non-toxigenic strains.…”
Section: Introductionmentioning
confidence: 99%